EVALUATION OF PHYSICAL AND MINERALOGICAL PROPERTIES OF GRAPHITE-MODIFIED BITUMEN - Lawal, Mamadu; Joseph, Oyedepo Olugbenga; Omoniyi, Olukanni Ebenezer; Jayejeje, Omomomi Oladapo (Journal of Civil Engineering, Science and Technology, 2024)
This study aimed to investigate the impact of adding graphite on the physical and mineralogical properties of bitumen in asphalt mixtures, covering a graphite content ranging from 0% to 8%. A variety of tests were conducted to assess these effects, including measurements of softening point, flash and fire values, ductility point, Marshall stability, Marshall flow, and indirect tensile strength. Evaluations also encompassed assessments of particle size distribution through coefficients of uniformity (Cu) and gradation (Cc), aggregate strength via Aggregate Crushing Value (ACV) tests, and impact resistance with Aggregate Impact Value (AIV) tests. The results indicated a desirable well-graded particle size distribution in the soil sample, with Cu and Cc values of 4.5 and 0.5, respectively. The aggregate showed a satisfactory ACV of 28.91%, falling within the recommended range, and an AIV value of 19.84%, meeting road surfacing specifications. Adding graphite to bitumen increased the softening point, reaching a maximum value of 54.1°C at 8% graphite content. This addition also improved flash and fire values, with peak levels at the same graphite content. Furthermore, including graphite led to an enhanced ductility point, indicating improved flexibility. The graphite-modified asphalt concrete exhibited higher Marshall stability and flow, with optimum values of 18.09 kN and 3.80 mm, respectively, at 8% graphite content. The optimum indirect tensile strength of 986.20 kPa also occurred at 6% graphite content. XRD characterization confirmed the presence of various minerals in the unmodified bitumen, such as feldspars, pyroxenes, and quartz, which increased the specific surface area and reduced mechanical strength. In contrast, graphite-modified bitumen exhibited a modified structure with reduced specific surface area, and XRD patterns confirmed the presence of graphite, with a carbon content exceeding 85%. The study strongly recommends incorporating 6% graphite into asphalt mixtures, as this measure significantly enhances their performance and durability.